(untitled) (Jurnal Destinasi Pariwisata, 2026)
Cultural tourism is central to Indonesia’s economy and heritage preservation, and Taman Mini Indonesia Indah (TMII) is its largest cultural tourism venue. This study investigates how tourist satisfaction with services shapes revisit intention at TMII. A quantitative survey of 105 visitors administered from March to May 2025 employed the SERVQUAL framework to assess five service quality dimensions: tangibility, reliability, responsiveness, assurance, and empathy. Underpinned by Expectancy Disconfirmation Theory and the Theory of Planned Behavior. Simple linear regression was used to test whether overall service satisfaction predicts revisit intention. Results indicate a positive and statistically significant effect (t = 67.144, p < 0.001), with a coefficient of determination R² = 0.978, implying that service satisfaction explains 97.8% of the variance in revisit intention. These findings underscore the strategic importance of service excellence in sustaining loyalty at a flagship cultural destination. Practically, managers should prioritize visible facility maintenance and cleanliness, consistent and timely service delivery, prompt complaint handling, staff competence that builds trust, and empathetic, personalized interactions. Conceptually, the results align with ECT by showing that satisfaction arising from performance exceeding expectations strengthens intention to return, and with TPB by suggesting that favorable attitudes toward service quality translate into behavioral intentions. Future work could expand the model by incorporating destination image, price perceptions, or satisfaction with specific attractions, and by testing multi-group differences across visitor segments. Strengthening the five SERVQUAL dimensions at TMII can help secure repeat visitation and, by extension, support cultural preservation and tourism-driven economic benefits. Implications for policy are also discussed